Taiwan's Tzu Chi as engaged Buddhism origins, organization, appeal and social impact - Yao, Yushuang (Leiden ; Boston : Global Oriental, 2012)
This is the first comprehensive sociological study of a new Chinese Buddhist movement, known as Tzu Chi (otherwise, the Buddhist Compassion Merit Society). Based in Taiwan, it was founded in 1966 and is still led by a female Buddhist master - Master Cheng Yen. Its members are laity and its main focus is medical charity and education of the wealthy in an ethical way of life.
CHAPTER SEVEN: TZU CHI'S ORGANIZATIONAL STRUCTURE AND THE PROCESS OF SOCIALIZATIONImpersonal Organizational Structure; The Abode and Headquarters; The Tzu Chi Branches and Liaison Offices; Tzu Chi Overseas Centres; The Leadership of Master Cheng Yen; The Process of Socialization; The New Converts; The Grouping, Bonds of Affection and Seniority; The Process of Indoctrination; The Initiation Ceremony; Discussion and Problems; CHAPTER EIGHT: THE APPEAL OF TZU CHI BUDDHISM; The Initial Appeal; The Appeal of Tzu Chi as a Charity; Tzu Chi's Recruiting Strategy; The Quality of Tzu Chi's Members.
Includes bibliographical references and index.
The Curiosity Factor.
Description based on print version record.
Keywords: Fo jiao ci ji ci shan shi ye ji jin hui; Buddhism -- Taiwan -- History; Buddhism -- Social aspects; RELIGION / Buddhism / General; Electronic books